Mercury and silver in saliva from subjects with symptoms self-related to amalgam fillings - Lygre, G. B.; Høl, P. J.; Eide, R.; Isrenn, R.; Gjerdet, N. R. (Clinical oral investigations, 1999)
The amount of mercury released into saliva from dental amalgam fillings is currently being debated. Mercury enters saliva as vapor, ions and particles of amalgam. The aim of the present study was to determine mercury and silver concentrations in saliva of persons with amalgam fillings. Moreover, it was the aim to investigate whether amalgam particles were present in samples of stimulated saliva in control subjects. In that case, we also wanted to determine the influence of these particles on the mercury concentrations found. Fifty-three patients with a wide range of complaints self-related to their amalgam fillings were examined by the Dental Biomaterials Adverse Reaction Unit of Norway. Among other tests, stimulated saliva was collected from each patient and analyzed for mercury and silver. Mercury and silver correlated with the amount of amalgam present. There was a strong correlation between mercury and silver concentrations. Amalgam particles were found by energy dispersive X-ray analysis. It appears that a considerable part of the mercury and silver were present as amalgam particles. The present study shows that amalgam particles in saliva have to be controlled for when analyzing mercury in saliva from subjects with amalgam fillings.